MODERN HYDROCHEMICAL REGIME OF LAKE SYSTEMS OF THE LOWER DELTA OF THE ILE RIVER - Sharipova О.А. (Hydrometeorology and ecology, 2023)
The article presents the results of studies of the hydrochemical regime of the lakes of the lower delta of the river Ile. An analysis of the inter-annual dynamics of the chemical parameters of the water of the monitoring lakes of the Iyr-Maytan and Nauryzbai systems showed a decrease in the content of organic matter. The water of the lakes of the Iyr-Mitansky system is distinguished by the constancy of the ion-salt composition. The Nauryzbai system is characterized by considerable fluctuations in the mineralization of water, depending on the water level of the river Ile.